2022
DOI: 10.1186/s40798-022-00508-w
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Increased Total Protein Intake and Strength Training on Muscle Strength: A Dose-Response Meta-analysis of Randomized Controlled Trials

Abstract: Background Protein supplementation augments muscle strength gain during resistance training. Although some studies focus on the dose-response relationship of total protein intake to muscle mass or strength, the detailed dose-response relationship between total protein intake and muscle strength increase is yet to be clarified, especially in the absence of resistance training. Objective We aimed to assess the detailed dose-response relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…A recent review 28 found that in participants >65 years old undertaking resistance training, the addition of 1.2–1.59 g/kg protein intake resulted in higher increases in lean mass than did lower protein intake. A review of resistance training interventions 29 showed that increases in protein intake up to 1.5 g/kg resulted in an increase in muscle power. Among intervention trials involving >1.3 g/kg protein intake, lean mass continued to rise in studies with resistance training but declined without resistance training, even with increased protein intake 30 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent review 28 found that in participants >65 years old undertaking resistance training, the addition of 1.2–1.59 g/kg protein intake resulted in higher increases in lean mass than did lower protein intake. A review of resistance training interventions 29 showed that increases in protein intake up to 1.5 g/kg resulted in an increase in muscle power. Among intervention trials involving >1.3 g/kg protein intake, lean mass continued to rise in studies with resistance training but declined without resistance training, even with increased protein intake 30 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ]; an I 2 of 50%–56% for strength in Tagawa et al. [ 75 ]; and an I 2 of 90% or more for strength and physical function in Chang et al. [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the overall amount of dietary protein consumed daily appears to be the principal nutritional determinant of skeletal muscle anabolism. Though it was originally proposed that the Recommended Dietary Allowance (RDA) of 0.8 g protein/kg BW/day is sufficient for athletes, recent meta-analyses suggest that optimum adaptation occurs with intakes of ~1.6 g protein/kg BW/day when paired with appropriate exercise training, though intakes upwards of ~2.2 g protein/kg BW/day may be warranted in certain cases [ 11 , 12 , 37 , 38 , 39 ]. Consistent with the most recent evidence, the UEFA expert panel advises intakes of 1.6–2.2 g protein/kg BW/day for soccer players [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consensus report authored by FIFA/FIFA-Medical Assessment Research Center (F-MARC) in 2006 specifies that a maximum of 1.2–1.6 protein/kg BW/day may be needed by soccer athletes, though stating that the evidence of this is “not clear or universal” [ 10 ]. By comparison, more recently issued soccer-specific sports nutrition guidance by an expert group commissioned by the Union of European Football Associations (UEFA) recommends protein intakes in the range of 1.6–2.2 g/kg BW/day [ 3 ], in concert with accumulating evidence that these intakes maximally augment the skeletal muscle adaptive response to exercise training [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%